Penolakan Rupiah dalam Era Cashless: Studi terhadap Merchant QRIS dan Dekriminalisasi - Irwan Hidayat; Rosa Tedjabuwana (Jurnal Hukum Lex Generalis, 2026)
This study is motivated by the increasing use of digital payment systems through QRIS which has led to the practice of refusing cash payments by merchants, raising legal issues regarding the relevance of criminal sanctions under the Currency Law. The results show that refusal of cash payments by QRIS merchants does not automatically constitute a criminal offense as long as Rupiah remains the unit of transaction value. The conclusion emphasizes that appropriate legal policy is decriminalization through strengthening administrative sanctions, consumer protection mechanisms and the regulation of cash thresholds by positioning criminal law as an ultimum remedium.